Jugendkommunikation und Dialekt Syntax gesprochener Sprache bei Jugendlichen in Osttirol - Lenzhofer, Melanie (Empirische Linguistik / Empirical Linguistics, 2017)
By examining communication among young people in East Tyrol, this study offers for the first time detailed insight into everyday conversation between Austrian adolescents. The central theme of this corpus-based analysis is to discover the areas of syntactic variation in which one can detect preferential use of particular syntactic constructions by adolescents and the role played by specific dialectical features of Bavarian.